Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI) : Status of Implementation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This report provides an update on the status of implementation, impact and costs of the enhanced Heavily Indebted Poor Country (HIPC) Initiative and the Multilateral Debt Relief Initiative (MDRI) since mid-2006. It also discusses the status of creditor participation in both initiatives and the issue of litigation of commercial creditors against HIPCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet